2014
DOI: 10.1007/s12094-014-1249-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiling of microRNAs in para-carcinoma, carcinoma and relapse human pancreatic cancer

Abstract: The differential expressed miRNAs and their predicted target genes that involved in Jak-STAT signaling pathway, MAPK signaling pathway and PPAR signaling pathway indicating their potential roles in pancreatic carcinogenesis and progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In almost all malignancy studies, microRNA (miRNAs) are found especially critical because they can be the results of chromosome lesions, modulated by classic cell signaling, and they themselves can act as both oncogenes and tumor suppressors ( Bartel, 2004 ; Lan et al, 2015 ). Recently, a close association between miRNAs and pancreatic cancer tumorigenesis has been elucidated ( Lai et al, 2015 ; Pavlakis et al, 2013 ). Various miRNAs, such as miR-200 ( Yu et al, 2010 ), miR-146a ( Li et al, 2010 ), miR-486 ( Mees et al, 2009 ) and the let-7 family ( Li et al, 2009b ) have been confirmed to be tumor suppressors; meanwhile, pancreatic cancer malignancy was found positively associated with miR-196a ( Huang et al, 2014 ), miR-212 ( Ma et al, 2014 ) and miR-31 ( Laurila et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In almost all malignancy studies, microRNA (miRNAs) are found especially critical because they can be the results of chromosome lesions, modulated by classic cell signaling, and they themselves can act as both oncogenes and tumor suppressors ( Bartel, 2004 ; Lan et al, 2015 ). Recently, a close association between miRNAs and pancreatic cancer tumorigenesis has been elucidated ( Lai et al, 2015 ; Pavlakis et al, 2013 ). Various miRNAs, such as miR-200 ( Yu et al, 2010 ), miR-146a ( Li et al, 2010 ), miR-486 ( Mees et al, 2009 ) and the let-7 family ( Li et al, 2009b ) have been confirmed to be tumor suppressors; meanwhile, pancreatic cancer malignancy was found positively associated with miR-196a ( Huang et al, 2014 ), miR-212 ( Ma et al, 2014 ) and miR-31 ( Laurila et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are particularly important in almost all tumor developmental processes since they can be targets of genomic lesions, controlled by classic tumor signals, and they themselves present as a class of oncogenes or tumor suppressors (3,4). Recently, a close association between miRNAs and lung cancer tumorigenesis has been suggested (5,6). Multiple miRNAs, such as the let-7 family (7), miR-200 (8), miR-486 (9) and miR-146a (10) have been identified as tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a close association between miRNAs and PDAC tumorigenesis has been elucidated [5,6]. Various miRNAs, such as miR-200 [7], miR-146a [8], miR-486 [9], and let-7 family [10] have been confirmed to be tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%